(untitled) (Revista Apotheke, 2021)
The purpose of this study is to reflect on the dimension of experience in art, art and art from its relational context of knowledge construction. Such a path can be powerful in affecting the senses for significant training experiences in the process of teaching and learning about the art. The investigation focused on experiences in the field of art where it was possible to identify crossings with education. The creation processes of artists such as Joseph Beuys, Marcel Duchamp, Bazon Brock, Helio Oiticica, Lygia Clark, Pablo Helgueira and Ricardo Basbaum reveal ways of taking on art in which the dimension of education is present, whether in action and/or thought, that in very particular ways. In this context, the role of the public is discussed, discussing its place of perception, observation and participation in the works. John Dewey (2010) is taken as a reference in the understanding of the concept of art as experience, and debates about creation processes in art and in education are developed from authors such as Cecília Almeida Salles (1998) in other dialogues with contemporaneity